Exceptional 30-year survival of a patient with multiple myeloma – quality of life and management of disease-related symptoms - Lebowa, Patrycja; Lebowa, Weronika Marzena; Jurczyszyn, Artur (Medycyna Paliatywna/Palliative Medicine, 2024)
Multiple myeloma (MM) is a chronic plasma cell malignancy with a median survival of about 8–10 years. Despite the development of many new drugs in recent years, disease recurrence is inevitable. The current critical unmet need is the management of heavily pretreated patients with refractory MM. We present the case of a 65-year-old male patient with an exceptionally long-term 30-year course of MM treated with 13 treatment lines. The patient struggles with many disease-related symptoms and treatment toxicity. The patient is currently treated with a triplet regimen including isatuximab, pomalidomide, and dexamethasone. Overall survival of 30 years, which is 3 times greater than the median survival in MM, is still rare, but achievable. In addition to anticancer treatment, supportive care is very important to alleviate myeloma symptoms and improve quality of life. To our knowledge, this is one of the published clinical cases with the longest survival in MM.